Circulating Endothelial Progenitor Cells is a predictor in Atherosclerosis: Is it really a promising candle? - Anwar Santoso (The Indonesian Heart Association, 2013)
Circulating endothelial progenitor cells (CEPC) are supposed to be a subset of bone marrow-derived peripheral blood mononuclear cells (PBMC), revealing immature surface markers common to hematopoietic stem cells, such as CD 34 and CD 133 and endothelial lineage markers. These cells can be isolated from peripheral, umbilical cord, and bone marrow blood. CD 34 represents a marker of immature stem cells that is commonly used to characterize CEPC together with other surface antigens. Though, as CD 34 is also expressed at lower levels on mature endothelial cells, most recent studies used CD 133, a marker of more immature hematopoietic stem cells that is now considered the best surface marker to define, identify and isolate the CEPC1. CD 133 (also known as AC 133 or prominin) is highly conserved antigen with unknown biological activity. It would be expressed on hematopoietic stem cells, but not on mature endothelial cell and monocytes. In order to reflect the endothelial cells, there is general agreement for the use of at least one additional marker, such as vascular endothelial growth factor receptor-2 (VEGFR-2 or KDR), while others are platelet-endothelial cells adhesion molecules-1 (PECAM-1), von Willebrand factor, c-kit, Tie-2, vascular endothelial-cadherin and VEGFR-12.